Changes in the prevalence of hepatitis B and C viral infections in Sindh province, Pakistan: Findings from two sero‐surveys in 2007 and 2019 - Alamneh, TS; Walker, JG; Lim, AG; Alam, E; Hamid, S; Foster, GR; Choudhry, N; Ansari, MA; Qureshi, H; Vickerman, P (Wiley, 2024)
Pakistan harbours a large burden of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. We utilised repeat sero‐surveys to assess progress achieved towards hepatitis elimination in Pakistan. Multilevel logistic regression evaluated the change in HBV infection (HBV surface antigen (HBsAg)‐positive) prevalence and HCV exposure (HCV antibody (HCV‐Ab)‐positive) prevalence between two sero‐surveys from 2007 and 2019 for Sindh province and associated risk factors. Adjusted odds ratios (aORs) were estimated and population‐attributable fractions (PAF) for modifiable risk factors for HCV exposure. The 2007 and 2019 surveys included 8855 and 6672 individuals. HBsAg prevalence decreased from 2.6% (95% confidence intervals (95% CI): 2.2–2.9) in 2007 to 1.1% (95% CI: 0.8–1.3) in 2019, while HCV‐Ab prevalence increased from 5.1% (95% CI: 4.6%–5.5%) to 6.2% (95% CI: 5.6%–6.8%). The age and gender‐adjusted HBsAg prevalence decreased by 80% (aOR = 0.2, 95% CI: 0.1–0.4) among children and 60% (aOR = 0.4, 95% CI: 0.3–0.6) among adults over 2007–2019, while HCV‐Ab prevalence decreased by 60% (aOR = 0.4, 95%CI:0.2–0.7) in children and increased by 40% (aOR = 1.4, 95% CI: 1.2–1.7) in adults. HCV‐Ab prevalence was lower in adults with secondary (aOR = 0.6, 95% CI: 0.5–0.8) and higher (aOR = 0.5, 95%CI:0.3–0.8) education compared to illiterates and higher among adults reporting blood transfusion (aOR = 1.7, 95% CI: 1.2–2.4), family history of hepatitis (aOR = 2.5, 95% CI: 1.9–3.3), past year medical injection (aOR = 2.1, 95% CI: 1.6–2.7), being tattooed (aOR = 1.4, 95% CI: 1.0–1.9) and shaved by traditional barber (aOR = 1.2, 95% CI: 1.0–1.5). Modifiable risk factors accounted for 45% of HCV exposure, with medical injection(s) accounting for 38% (95%CI,25.7–48.4%). Overall HCV has increased over 2007–2019 in Sindh province, while HBV prevalence has decreased. Medical injections should be an important focus of prevention activities.